Correlations between cognitive assessment and RNFL changes in OCT in healthy aging subjects. (31st December 2021) - Shen, Ting; Sheriff, Samran; Schulz, Angela; You, Yuyi; Graham, Stuart; Gupta, Vivek K
Abstract: Background: The retinal nerve fibre layer (RNFL) comprises retinal ganglion cell axons and link the outer neuroretina to the higher visual cortex. The retina is the only part of the central nervous system that can be visualised directly and non‐invasively by optical coherence tomography (OCT). The study aimed to examine whether changes in the visual pathway are correlated with various domains of cognitive function assessment. We evaluated correlation between retinal structural (OCT) and neuropsychological (trail making test, TMT; Boston naming test, BNT) measures in healthy aging subjects. Method: In the present cross‐sectional clinical study, 74 healthy aging subjects were recruited from the Optic Nerve Decline and Cognitive Changes (ONDCC) study. All participants underwent OCT peripapillary ring scan protocol for RNFL analysis, TMT testing for attention and executive function and BNT neuropsychological examination for the detection of word‐retrieval or naming difficulties. Averaged RNFL thickness measures were used to analyse the relationship with TMT and BNT. Correlations between TMT, BNT and OCT parameters were analysed using partial correlation and controlled for age and gender (P < 0.05). Result: The mean (SD) age of the current cohort is 67.5 (± 9.0 years). At baseline, significant correlation was observed between TMT‐test A and nasal RNFL thickness (r = ‐0.33, P = 0.009). The BNT also demonstrated mild but significant positive correlations with global (r = 0.32, P = 0.01), nasal (r = 0.27, P = 0.03) and nasal inferior (r = 0.33, P = 0.01) sectoral RNFL thicknesses respectively. Conclusion: The results indicated a significant correlation between RNFL thickness and executive function domain of cognitive assessment. Sectoral RNFL was also significantly correlated with naming ability (BNT) across the cohort of healthy elderly. These findings suggest that the RNFL measures may parallel cognitive decline in the aging population. Further studies are planned in confirmed cognitively impaired subjects.